Energy resources and their effects on environment - (:unkn) unknown (My University, 2010)
The World Energy Committee states that there exists no risk free energy resource and for this reason, while choosing the energy resources, cost factors must be considered with environmental effects. Today, prevention of environment pollution and conservation of environment have a dimension exceeding national borders. The risks that result from using of fossil fuels increasingly (petroleum, coal, gas) must be decreased (air pollution, thinning of ozone layer, acid rains etc). To decrease such risks, besides to increasing of energy productivity, energy resources that emit less sera gas in the atmosphere (like Carbon-dioxide (CO2)) must be preferred. Otherwise, destruction of ecological balance and disasters in future will be inevitable. The negative effects of renewable energy resources on environment are lesser than the conventional energy resources. Costs of renewable energy resources are lesser than the fossil origin fuels. They never consume as they are renewable and in contrary to the conventional fuels, they do not exhibit a significant threat for environment and human health. In this study, effects of energy resources on environment are considered in detail. Especially, effects of renewable energy resources on environment and criteria that must be observed in energy production to prevent environment pollution are examined.
Keywords: Energy; Environment; Fossil fuels; Global warming; Nuclear power plants; Renewable energy